Integrating The History of Mathematics in Secondary Classrooms: A Practical Pedagogical Approach - Zhou Yini ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2026)
Despite extensive theoretical recognition of the History of Mathematics (HPM) in enhancing mathematics education, a persistent gap remains between scholarly advocacy and classroom implementation in Chinese secondary schools. This study aims to bridge this theory-practice divide by investigating the status of HPM integration and proposing actionable pedagogical strategies. A mixed-methods approach was employed, combining a questionnaire survey of 285 students across three grades and semi-structured interviews with all 26 mathematics teachers at Chongxian Middle School in Yongchun County, Fujian Province. Quantitative data were analyzed using SPSS to examine student attitudes and knowledge acquisition, while qualitative interview data revealed teachers' self-reported familiarity with historical content (only 7.8% "very familiar"), dominant reliance on textbook-derived knowledge (56.3%), and infrequent classroom application (40.9% "seldom" or "never"). The findings indicate that although 77.9% of students affirmed the pedagogical value of HPM, teachers' actual integration remained largely superficial, primarily through lecture-based storytelling rather than inquiry-oriented activities. Based on these results, the study proposes a framework of four integration principles and five practical methods—multimedia presentation, storytelling, situational drama, thematic discussion, and task-based inquiry—exemplified through a redesigned Pythagorean Theorem lesson. This research contributes concrete instructional designs to advance HPM from theoretical endorsement to effective classroom practice.